Feasibility of pre-treating wastewater/water to prevent/minimize reverse osmosis (RO) membrane biofouling using UV process - Tang, Wan Chiao (2017)
Ultraviolet (UV) light has been proven as an effective Advanced Oxidation Processes (AOPs) for disinfection. Furthermore, this method has been tested in combining with other AOPs to assess its efficiency. Hybrid systems have proved effective in one way or another. In this thesis, UV light with different power outputs is tested on inactivating microorganisms in wastewater before pre-treatment. The main purpose of this thesis is to explore ways to reduce bio fouling and thereby extend the life of membrane. This study used 2.5W and 1.0W submerged UV lamps to disinfect 104, 105, 106, 107 CFU/ml of pseudomonas aeruginosa. Through this experiment, we concluded that higher power lamp is more efficient in inactivating pseudomonas aeruginosa, however economic cost is another issue that needs to be considered. Moreover, we discovered that the kinetic constant k is estimated to be 0.0254 ± 0.0022s-1 and 0.121 ± 0.0204s-1 for 1.0W and 2.5W respectively. The energy yield is the highest for 107 CFU/ml of pseudomonas aeruginosa. Also, the results show no reactivation of pseudomonas aeruginosa. Due to the time constraint, the performance of UV on pre-treating membrane was not carried out and it is recommended to be done in the near future.